Palm Claws Pro Machine - Abdullah, Muhammad Adam; Noor Azam, Muhammad Noor Azamuddin; Maz Azri, Izzul Hafiz; Mohammad Noor, Hafsa (Multidisciplinary Applied Research and Innovation, 2025)
The palm oil industry has been vital to Malaysia’s economy since 1848, significantly impacting both local and international markets, especially in the European Union. However, the industry struggles with the mechanization of the harvesting process. Many Malaysian farmers still rely on manual tools to lift palm fruit bunches (FFB), which can weigh up to 20 kg. This manual labor often leads to musculoskeletal disorders and injuries due to physical strain and poorly designed tools. This report introduces the Palm Claws Pro (PCP), a machine designed to lift and load fresh fruit bunches onto trucks, reducing the physical burden on workers and improving workplace safety. The project aims to create a user-friendly machine that requires minimal training, assess its safety effectiveness, and compare its performance with traditional methods. The PCP machine was meticulously designed and tested to meet ergonomic needs. The grabber can lift FFB to a height of 1.79 m without hydraulic assistance, allowing for easy transfer onto standard truck platforms. The machine’s robust design can handle the weight of a 20 kg bunch without damage, thus maintaining operational reliability. Testing revealed that the PCP machine significantly reduces the time and effort needed to load FFB compared to manual methods. This efficiency improvement not only enhances productivity, lowers transportation costs, and enhances logistics in palm oil distribution. Moreover, using the PCP machine is expected to decrease absenteeism and labor turnover by reducing work-related injuries, creating a safer work environment. The Palm Claws Pro machine provides a practical solution to challenges in the palm oil industry. By alleviating physical strain on workers and increasing efficiency, the PCP machine supports a healthier workforce. Future enhancements could include a hydraulic jack for heavier loads, a handle for better mobility, and a more powerful motor for improved gripping strength.